Exact Solutions for a GBM‐Type Stochastic Volatility Model Having a Stationery Distribution. Issue 101 (17th May 2019) - Lewis, Alan L.
Abstract : Alan Lewis discusses the background to the Extended Geometric Brownian Motion model introduced in this issue.